Dampak Tata Kelola Perusahaan yang Baik terhadap Earning per Share pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021-2023 (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyze the relationship between corporate governance and Earning per Share, which uses five independent variables, namely Managerial Ownership (MO), Foreign Ownership (FO), Audit Committee (AC), Board of Commissioners Size (BOS), and Independent Commissioners (IC). Meanwhile, the dependent variable used is Earning per Share (EPS). This research data is secondary, with a population of 25 companies in the food and beverage sub-sector on the Indonesia Stock Exchange (IDX). Then, out of 25 companies, 14 companies the criteria, so there were 42 samples during the 2021-2023 period with a purposive sampling technique. This test method uses Quantitative and as a test using Multiple Linear Regression and is processed using a statistical test application. The results obtained by Managerial Ownership on Earnings per Share have no effect, Foreign Ownership is also proven not to affect Earnings per Share, the Audit Committee does not contribute to Earnings per Share, the Size of the Board of Commissioners has a positive influence on Earnings per Share, Independent Commissioners are also not proven to influence Earnings per Share. These findings indicate that an optimal board of commissioner’s structure can increase the effectiveness of supervision and support the efficiency of decision making, thereby having an impact on increasing Earnings per Share.